2007
DOI: 10.3177/jnsv.53.160
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Dimethyl Sulfoxide (DMSO) on Necrosis and Oxidative Stress Caused by D-Galactosamine in the Rat Liver

Abstract: Summary D -Galactosamine ( D -Galn: 300 mg/kg) was intraperitoneally administered to rats. After 6 h the activity of plasma GOT and GPT was significantly higher than that of the control group and plasma GOT and GPT activities increased thereafter. These results indicated that the necrotic process was initiated at about 6 h and developed thereafter. With coadministration of DMSO (1 h before administration of D -Galn: 2.5 mL/kg, oral), plasma GOT and GPT were significantly lower, showing that DMSO inhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The cascade of activities initiated by LPS intoxication leads to disruption of structural integrity of the hepatic cell membrane and release of SGOT, SGPT, ALP, lactate dehydrogenase (LDH) and alkaline phosphatase (AP) hepatic non-specific enzymes into the blood stream from the affected, necrotic and dead hepatocytes and possible hepatic dysfunction manifested by increased serum total bilirubin, thus producing signs of hepatotoxicity. 26,27 In the present study, the observation of elevated level of serum SGOT, SGPT, ALP and total bilirubin in the group of mice treated with LPS alone is consistent with these reports and might explain the inflammation manifested in liver. Earlier reports state that supplementation of natural antioxidants were proven to be an excellent prevention strategy for many diseases, including diabetes liver injury, liver fibrosis, cancer and ageing.…”
Section: Discussionsupporting
confidence: 91%
“…The cascade of activities initiated by LPS intoxication leads to disruption of structural integrity of the hepatic cell membrane and release of SGOT, SGPT, ALP, lactate dehydrogenase (LDH) and alkaline phosphatase (AP) hepatic non-specific enzymes into the blood stream from the affected, necrotic and dead hepatocytes and possible hepatic dysfunction manifested by increased serum total bilirubin, thus producing signs of hepatotoxicity. 26,27 In the present study, the observation of elevated level of serum SGOT, SGPT, ALP and total bilirubin in the group of mice treated with LPS alone is consistent with these reports and might explain the inflammation manifested in liver. Earlier reports state that supplementation of natural antioxidants were proven to be an excellent prevention strategy for many diseases, including diabetes liver injury, liver fibrosis, cancer and ageing.…”
Section: Discussionsupporting
confidence: 91%
“…Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Potential limitations of these studies, as acknowledged by the investigators [21,22] is that JNK inhibitors may not be specific and as reported can affect other signaling events that could lead to the misinterpretation of results [36][37][38][39]. Further, some of the JNK inhibitors were dissolved in vehicles containing DMSO [14,21] and polyethylene glycol [22,35], which may affect various parameters at the cellular and molecular level [34,[40][41][42][43].In conclusion, our findings suggest that JNK2 plays a protective role against AILI in mice at least, in part, by modulating hepatocellular regeneration and repair. Although other research in mice provides evidence for JNK having a pathologic role in AILI, we feel that it is prudent to reconsider the use of JNK inhibitors as a therapeutic intervention in AILI [21,22,35,44].…”
mentioning
confidence: 99%
“…However, DMSO treatment did not affect the change of MAPKs by D -Galn (Iida et al 2007b ). However, DMSO treatment did not affect the change of MAPKs by D -Galn (Iida et al 2007b ).…”
Section: Hepatitis Caused By D -Galactosamine ( D -Galn)mentioning
confidence: 73%